Managing Innovation in the Modern Business Environment - Šebalj, Luka; Veselica Celić, Rozana (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The evolution of digital communication tools has significantly transformed interactions within organizations, fostering innovation and redefining management practices in modern business contexts. This research examines the adoption, challenges, and opportunities of digital communication tools, emphasizing their role in enhancing productivity, global connectivity, and interpersonal relationships. A survey conducted among students and professionals revealed high adoption rates of digital tools. Respondents identified key benefits, including speed, efficiency, and accessibility, while also highlighting concerns regarding security, privacy, and technical reliability. These findings emphasize the necessity for innovative management strategies to optimize the selection and integration of digital tools, addressing both functional and security challenges. By effectively navigating these complexities, organizations can leverage digital tools to foster innovation, streamline operations, and enhance collaboration. This study provides valuable insights into the intersection of innovation and management, guiding strategic decisions and future research initiatives.